Supply Chain Management Resilience: How It Works To The Sustainability of Culinary SMEs Through Decade - Dian Inda Sari; Rizky Saputra; Dewa Handinata (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: The culinary industry has become a favored choice for startup entrepreneurs, primarily due to its accessibility and the potential for immediate financial returns. However, it's essential to recognize that success in this domain hinges on proactive and well-considered strategies and actions. Entrepreneurs must employ these strategies, including effective Supply Chain Management (SCM), to ensure customer satisfaction. Purpose: The objective is to investigate the relationship between these four factors and the performance dimensions of culinary SMEs that manage to sustain their operations for at least a decade. Design/methodology/approach: This study adopts a quantitative research approach to assess the resilience of Culinary SMEs SCM, with a focus on the variables of agility, robustness, flexibility, and service quality. Structural Equation Modeling (SEM) with Smart PLS is used to examine the research hypothesis model.Findings/Result: The findings from data analysis reveal that these four variables have a positive impact on the performance of culinary SMEs that have successfully operated throughout the decade. Conclusion: SCM resilience plays a pivotal role in helping Culinary SMEs navigate the prevailing uncertain business landscape while maintaining their competitive edge. It has been revealed that SCM resilience has a constructive impact on the long-term performance of Culinary SMEs, a resilience that can withstand the test of time. Originality/value (State of the art): The state-of-the-art research is to develop an SCM framework starting from the primary inquiry: how can Culinary SMEs segment materials to facilitate smoother supply processes? The research also explores how such segmentation can enhance Culinary SMEs' resilience and logistics strategies. This necessitates establishing priorities to ensure service quality, ultimately leading to the identification of key SMEs Culinary SCM resilience performance by using four variables measures. Keywords: culinary smes scm, scm resilience, scm agility, scm flexibility, service quality